El trabajo infantil y sus repercusiones en el desarrollo integral de las personas menores de edad - María Ester Morales-Ramírez (Universidad Nacional, Costa Rica, 2003)
This article considers the impact of child labour (Child work exploitation) in the adequate integral development of boys, girls and teenagers, specifically on aspects related to their physical, emotional, social, moral and cognitive growth. This type of activity shows serious consequences when youngsters abandon the educational system to dedicate their time to work. This peper points out child labour as one of the main causes of explotation and chil abuse in this population group, and questions our role, as citizens, towards the management of this situation.